2004
DOI: 10.1080/09638280410001714772
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric validation of a subjective well-being measure for people with spinal cord injuries

Abstract: The factorial validity and the concurrent validity of the SWBI were generally supported. The SWBI, as a subjective well-being measure developed specifically to relate to disability and rehabilitation, appears useful for use with people with SCI in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 17 publications
2
57
1
1
Order By: Relevance
“…Most authors clearly distinguish their instrument or definition of QOL as objective 5,16,[18][19][20] or subjective. 1,6,9,20,21 Where no distinction was specified, instruments were classified according to the authors' definition of QOL 7 and/or the item content and scoring model. 22,23 For example, instruments addressing HRQOL or the presence, severity, and impact of specific health factors relating to QOL were considered objective, and instruments measuring life satisfaction or using scoring relationships between satisfaction and importance were classified as subjective.…”
Section: Classifying the Instrumentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most authors clearly distinguish their instrument or definition of QOL as objective 5,16,[18][19][20] or subjective. 1,6,9,20,21 Where no distinction was specified, instruments were classified according to the authors' definition of QOL 7 and/or the item content and scoring model. 22,23 For example, instruments addressing HRQOL or the presence, severity, and impact of specific health factors relating to QOL were considered objective, and instruments measuring life satisfaction or using scoring relationships between satisfaction and importance were classified as subjective.…”
Section: Classifying the Instrumentsmentioning
confidence: 99%
“…[4][5][6][7][8][9] It is clear that simple outcomes-assessing function are insufficient in measuring rehabilitation after SCI 7,9 and in capturing the adaptation of perceptions and values in patients after SCI. 7,9 In fact, it has been suggested that high levels of QOL is synonymous with positive rehabilitation outcomes, and many agree that QOL should be measured in tandem with traditional outcomes assessing functional rehabilitation. 9,10 Such measurements provide different yet complimentary information that aid clinicians in their efforts to help those with SCI.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations